2010
DOI: 10.1038/nrurol.2010.6
|View full text |Cite
|
Sign up to set email alerts
|

The effect of obesity on sperm disorders and male infertility

Abstract: The results of several studies point to an increased likelihood of abnormal semen parameters among overweight men, and an elevated risk for subfertility among couples in which the male partner is obese. Obesity is, therefore, associated with a higher incidence of male factor infertility. Several mechanisms might account for the effect of obesity on male infertility, both directly and indirectly, by inducing sleep apnea, alterations in hormonal profiles (reduced inhibin B and androgen levels accompanied by elev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
261
0
8

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 344 publications
(300 citation statements)
references
References 62 publications
9
261
0
8
Order By: Relevance
“…47 Obesity, a consequence of high caloric load induced by a high-energy diet, is associated with increased number and size of adipocytes, and thus many proposed mechanisms for the role of obesity in male infertility focus on the abnormal level of adiposederived hormones and adipokines. 85 It has been reported that obese men seeking infertility treatments show a decreased ratio of testosterone to estrogen. 86 This dysregulation is explained by the increased activity of aromatase cytochrome P450 enzyme, which is highly expressed in white adipose tissue.…”
Section: Discussionmentioning
confidence: 99%
“…47 Obesity, a consequence of high caloric load induced by a high-energy diet, is associated with increased number and size of adipocytes, and thus many proposed mechanisms for the role of obesity in male infertility focus on the abnormal level of adiposederived hormones and adipokines. 85 It has been reported that obese men seeking infertility treatments show a decreased ratio of testosterone to estrogen. 86 This dysregulation is explained by the increased activity of aromatase cytochrome P450 enzyme, which is highly expressed in white adipose tissue.…”
Section: Discussionmentioning
confidence: 99%
“…Occupational exposure of testicles to heat also has deleterious effects on male fertility (Mieusset et al, 1987;Paul et al, 2008) as well as sporadic exposure (Rockett et al, 2001). The effects of obesity on semen quality are marked not only on the concentration of sperm, but also on DNA fragmentation (Kort et al, 2006), probably as a result of a high scrotal temperature and of an important hormonal disruption (Du Plessis et al, 2010). Mobile phone port to the belt, especially when using a hands-free kit (the emission of electromagnetic waves is more important during a call) could have an adverse effect on male fertility (Desai et al, 2009).…”
Section: Impact Of Environment On Sperm Dna Damagesmentioning
confidence: 99%
“…Th erefore, it seems that dysregulation of the hypothalamic-pituitary-gonadal (HPG) axis as a consequence of male obesity might further explain the increased risks of sperm disorders and infertility 7,[29][30][31] . Another key hormone produced by white adipose tissue is leptin the production of which increases with the amount of body fat and which plays a pivotal role in regulating the energy intake and expenditure.…”
Section: Th E Mechanisms Linking Obesity To Male Infertilitymentioning
confidence: 99%